Selective hydrogenolysis of carbon–oxygen bonds with formic acid over a Au–Pt alloy catalyst. Issue 18 (15th February 2017) - Wang, Liang; Zhang, Jian; Wang, Guoxiong; Zhang, Wei; Wang, Chengtao; Bian, Chaoqun; Xiao, Feng-Shou
Abstract : A CeO2 -supported Au–Pt alloy catalyst is highly efficient for selective hydrogenolysis of carbon–oxygen species using formic acid as the hydrogen source. Abstract : We reported selective hydrogenolysis of carbon–oxygen species over a CeO2 -supported Au–Pt alloy catalyst (Au–Pt/CeO2 ) using biomass-derived formic acid as the hydrogen source. The success of this reaction is reasonably attributed to the high efficiency of Au–Pt/CeO2 in the tandem steps of formic acid dehydrogenation and carbon–oxygen species hydrodeoxygenation.